Effect of low impact development retrofitting in Shenzhen Xincheng Park - TIAN Kun; GONG Yongwei; CHEN Shijie; REN Xinxin; LI Junqi; WANG Wenliang (Shenzhen Daxue xuebao. Ligong ban)
The storm water management model (SWMM) was used to evaluate the stormwater control effect of the low impact development (LID) retrofitting of the Xincheng Park in Shenzhen, Guangdong Province, China. The calibration and validation of the model parameters were carried out using the measured data. The control rate of individual rainfall runoff events, the peak flow control rate, the peak time and the volume capture ratio of annual rainfall runoff volume as well as the related influence factors were analyzed under the different conditions of rainfall. The peak flow control rate reached from 30.4% to 47.2%, and the peak time delayed from 17 to 26 min with a relatively smooth runoff process line after retrofitting for the different return-period rainfall events. For monitored rainfall events and continuous rainfall events, the volume capture ratio of annual rainfall runoff volume after retrofitting reached from 70.7% to 94.8%, and 79.8%, respectively, in two situations. The results indicate that LID retrofitting has good performance in reduction of runoff and peak flow in high return-period rainfall events, while the reduction effect on the total and peak runoff generated under low-frequency rainfall conditions is limited. The stormwater runoff control effect of low impact development retrofitting facilities in Xincheng Park is still significant under long-term operating conditions.